Structure–activity relationship study of angiotensin II analogs in terms of β‐arrestin‐dependent signaling to aldosterone production. Issue 2 (8th March 2016) - Valero, Thairy Reyes; Sturchler, Emmanuel; Jafferjee, Malika; Rengo, Giuseppe; Magafa, Vassiliki; Cordopatis, Paul; McDonald, Patricia; Koch, Walter J.; Lymperopoulos, Anastasios
Abstract: The known angiotensin II (AngII) physiological effect of aldosterone synthesis and secretion induction, a steroid hormone that contributes to the pathology of postmyocardial infarction (MI) heart failure (HF), is mediated by both Gq/11 proteins and β ‐arrestins, both of which couple to the AngII type 1 receptors (AT1 Rs) of adrenocortical zona glomerulosa (AZG) cells. Over the past several years, AngII analogs with increased selectivity ("bias") toward β ‐arrestin‐dependent signaling at the AT1 R have been designed and described, starting with SII, the gold‐standard β ‐arrestin‐"biased" AngII analog. In this study, we examined the relative potencies of an extensive series of AngII peptide analogs at relative activation of G proteins versus β ‐arrestins by the AT1 R. The major structural difference of these peptides from SII was their varied substitutions at position 5, rather than position 4 of native AngII. Three of them were found biased for β ‐arrestin activation and extremely potent at stimulating aldosterone secretion in AZG cells in vitro, much more potent than SII in that regard. Finally, the most potent of these three ([Sar 1, Cys(Et) 5, Leu 8 ]‐AngII, CORET) was further examined in post‐MI rats progressing to HF and overexpressing adrenal β ‐arrestin1 in vivo. Consistent with the in vitro studies, CORET was found to exacerbate the post‐MI hyperaldosteronism, and, consequently, cardiac function of the post‐MI animals in vivo. Finally, our data suggest that increasing the size of position 5 of the AngII peptide sequence results in directly proportional increases in AT1 R‐dependent β ‐arrestin activation. These findings provide important insights for AT1 R pharmacology and future AngII‐targeted drug development.